Collaborative Writing: It’s Influence towards Students’ Recount Text Ability - Amalia Solikhah, Nur (International Journal Corner of Educational Research, 2022)
The objective of this research was to know the influence of collaborative writing ability towards students’ recount text of the tenth class students or not. The total populations are 61 students’ in two classes. The writer take two classes, one class as the experimental class that was taught by using Collaborative Writing and the second class as the control class that is taught without Collaborative Writing. In conducting the research, the writer use experimental method, the writer use writing test or t-test to know the students’ writing ability by using Collaborative Writing. The students ask to describe their experience the test use recorded in students’ writing ability, and the writer use the scoring system propose by Yendra Pratial. The writer determine the average rates (x) and variant (s2) before use t-test formula. The average score of experimental class that is taught by using Collaborative Writing is x2ratio = 7.77, and the average score of controll class that is taught with direct instruction is x2ratio= 7.23. Rejected Ho if : x2ratio ≥ x2table (1-α) (k-3), for the significant level of 5% obtained: x2table = 7.81, for the significant level of 1% (α=0.01) obtain: x2table= 11.3. So the Ho is accepted. The sample of this research the writer use cluster random sampling technique, and to test the hypothensis in this research, the writer use a statistical formula of t-test. According to the result of the data analyzing, the writer found that > (=3.10 and =2.70 in significance level 1% and ttable= 2.02 in significance level 5%. It means that positive influence of collaborative writing towards students recount text ability